2017
DOI: 10.1177/1059840517727831
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Communication Between School Nurses and Adolescent Girls in Ile-Ife, Nigeria

Abstract: We examined information on pubertal changes provided by school nurses to adolescent girls, the methods, and media of communication. We also examined the challenges faced by the nurses in the course of communication. The study setting was five private high schools located in Ile-Ife, Nigeria. Participants were 10 school nurses and 420 school adolescent girls. Cross-sectional descriptive design was employed using quantitative and qualitative data collection methods. Results showed school nurses paid more attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
4
0
4
Order By: Relevance
“…Therefore, it is crucial to understand menstrual health as a tool for health promotion, and its promotion as something that also contributes to achieving gender equality ( 3 ) and increasing the population’s literacy on the subject ( 4 ) , which in turn reinforces the important role of health care and education in achieving this. It is known that nurses are professionals who assist women in all stages of life, including the school environment, in which nursing care is related to providing items for MHM ( 51 ) , carrying out actions of health education, promoting access to information about the physiology of puberty ( 52 ) and contributing to the creation of facilitating school environments that support adolescents to experience the menstrual period with dignity ( 40 ) . These actions can benefit people who menstruate and also constitute windows of opportunity to promote other aspects in the field of reproductive health that may be equally neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to understand menstrual health as a tool for health promotion, and its promotion as something that also contributes to achieving gender equality ( 3 ) and increasing the population’s literacy on the subject ( 4 ) , which in turn reinforces the important role of health care and education in achieving this. It is known that nurses are professionals who assist women in all stages of life, including the school environment, in which nursing care is related to providing items for MHM ( 51 ) , carrying out actions of health education, promoting access to information about the physiology of puberty ( 52 ) and contributing to the creation of facilitating school environments that support adolescents to experience the menstrual period with dignity ( 40 ) . These actions can benefit people who menstruate and also constitute windows of opportunity to promote other aspects in the field of reproductive health that may be equally neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Compete ao enfermeiro escolar (atuante em alguns países) apresentar habilidades nos vários métodos de comunicação com os adolescentes, para estabelecer programa de saúde escolar eficaz (28) , como também desenvolver um aprimoramento no uso da tecnologia digital para comunicação com a população adolescente (29) .…”
Section: Discussionunclassified
“…A tecnologia é uma extensão do nosso cérebro, uma maneira diferente de pensar, um instrumento para lidar em diversos contextos (28) . Estudo de ensaio clínico controlado randomizado, de método misto, desenvolvido nos Estado Unidos da América, com aplicação de um jogo digital entre estudantes do ensino médio para explorar o potencial do jogo Protagonismo de adolescentes na criação de um storyboard para um jogo digital sobre hanseníase Santos TA, Araújo B de FP de, Brandão Neto W, Araújo EV de, Vasconcelos EMR de, Monteiro EMLM virtual em atividades sociais, emocionais e desenvolvimento cognitivo na promoção do pensamento ético e considerações morais para tomada de decisão, verificou que os que participaram das discussões depois de jogar, apresentaram resposta mais complexas (29) .…”
Section: Discussionunclassified
“…As such, effective communication that is built on respect for patients also fosters trust in the healthcare system and improves satisfaction with the services provided (Negro et al 2020 ). To enable such effective communication between nurses and high school learners, a Nigerian study found that nurses themselves have to be trained to provide effective communication on HIV prevention regardless of their beliefs (Salau & Ogunfowokan 2019 ). Such communication can be aided by audio-visual materials which high schools can provide (Salau & Ogunfowokan 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To enable such effective communication between nurses and high school learners, a Nigerian study found that nurses themselves have to be trained to provide effective communication on HIV prevention regardless of their beliefs (Salau & Ogunfowokan 2019 ). Such communication can be aided by audio-visual materials which high schools can provide (Salau & Ogunfowokan 2019 ).…”
Section: Introductionmentioning
confidence: 99%